2010
DOI: 10.1017/s1461145710001057
|View full text |Cite
|
Sign up to set email alerts
|

Association study of a functional catechol- O-methyltransferase (COMT) Val108/158Met polymorphism and suicide attempts in patients with alcohol dependence

Abstract: Alcohol dependence is frequently associated with aggressive and suicidal behaviour. Genetic factors contribute to both behaviours. Candidate genes, related to suicide and aggression, include genes involved in serotonin, norepinephrine and dopamine pathways. The enzyme catechol-O-methyl transferase (COMT) degrades dopamine, epinephrine and norepinephrine. The functional polymorphism (COMT Val108/158Met) affects COMT activity, with the valine (Val) variant associated with higher and the methionine (Met) variant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 63 publications
3
22
0
1
Order By: Relevance
“…With regard to the literature search, a total of 18 papers were identified, but only 12 were included in this meta-analysis, including our case-control study [1,5,29,33-40] (Table 1). The six excluded studies did not comply with the inclusion criteria: in two of these studies genotype frequencies could not be obtained [24,25]; other study was carried out in families [41]; in other report the sample overlapped with a previous one [26]; the fifth was a meta-analysis [11], and the sixth a review [42].…”
Section: Resultsmentioning
confidence: 99%
“…With regard to the literature search, a total of 18 papers were identified, but only 12 were included in this meta-analysis, including our case-control study [1,5,29,33-40] (Table 1). The six excluded studies did not comply with the inclusion criteria: in two of these studies genotype frequencies could not be obtained [24,25]; other study was carried out in families [41]; in other report the sample overlapped with a previous one [26]; the fifth was a meta-analysis [11], and the sixth a review [42].…”
Section: Resultsmentioning
confidence: 99%
“…(109). The Met/Met genotype has lower enzyme activity and is associated with higher levels of aggression and incidence of suicide attempts in schizophrenics and alcoholics (80,85). These studies should be viewed with caution, however, because of the small sample sizes, differences in gender, patient history, environmental conditions, and heterogeneity of psychiatric manifestations.…”
Section: Hormonal Regulation Of Aggressionmentioning
confidence: 99%
“…Although the regulatory role of genes in metabolism/signaling involved in the pathogenesis of depression (Opmeer, Kortekaas, & Aleman, 2010) and suicide behaviors (Tovilla-Zarate et al, 2011) has been reported, studies of its role in substance users are still lacking. To the best of our knowledge, only (Nedic et al, 2011) has reported that the Met allele of COMT Val108/158 Met is a potential biomarker of suicidal behavior among patients with alcohol dependence. This study revealed no involvement of the COMT and DAT1 gene variants in the pathogenesis of DIM and suicide attempts among illicit drug users.…”
Section: Discussionmentioning
confidence: 99%